PENGARUH STATUS KEPEGAWAIAN DAN TUNTUTAN PROFESIONALISME TERHADAP PENGUPAHAN TENAGA KESEHATAN - Lesmana, Lilis Christine; Dwinijanti, Lenny; Setiawan , Leonathan; Prayuti, Yuyut (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
In many cases, the wages of health workers are still below the average regional/provincial minimum wage (UMR/UMP). This can have an impact on the motivation and fulfilment of health workers' performance standards. In addition, the high level of risk in the work environment requires physical and spiritual fitness which costs money. Based on these problems, this research tries to examine the influence of employment status and demands for professionalism on the wages of health workers for nursing health workers, who have the largest number in both government and private institutions. This type of research is normative-empirical, the data used is secondary data. Secondary data was obtained from library research sourced from Institute reports, official government statistics, regulations as primary, secondary, and tertiary legal sources. From the results of the study, information was obtained that employment status and professional responsibilities have a significant influence on wage standards in the form of salaries and allowances for ASN/PPPK which are regulated in applicable laws and regulations. Meanwhile, in private institutions, the amount is regulated in the non-employee agreement for state civil servants (private sector), given in accordance with the work agreement or collective work agreement.